Corporate Social Responsibility During Gas Exploration Phase In Remote Areas of Papua: a Competitive Stakeholder Theory - Pongtiku, Arry; Zain, Djumilah; Thoyib, Armanu; Rahayu, Mintarti (Jurnal Aplikasi Manajemen, 2010)
This study used mixed methods: Grounded Theory of Mode 2 which focused on application for management science and supported by Experimental Design. It is resulted â€ A Competitive Stakeholder Theoryâ€ with Theoretical Propositions are 1) CSR (Triple Bottom Line philosophy) and Stakeholder Theory are competing theories considered as strategic management to achieve objectives through value maximizing. The goal of Stakeholder Theory is pro all stakeholders involved. Every stakeholder including shareholder shares and creates values together which are useful for themselves. 2) Stakeholder Theory is a dynamic process that contributed by Power and Control of Stakeholders embedded in ethics/philosophy; Existing Issues; Cost Effective Strategies; Moral and Trust; PDCA (Plan-Do-Check-Act); Recognition and Creating Values. They are a continuous process and have an interrelated relationship. In addition, pre and post interventions in society showed dramatically in reducing communicable diseases. Workplace performed high productivity among workers. Good overall score of Malcolm Baldrige Score Card indicated the quality management of this CSR was in place. It is suggested this Stakeholder Theory would be applied at stable situation and at unstable situation such as uncertainty, turbulence, limited resources, remote areas, minimizing risk and issues of social responsibility. Although the CSR implemented in exploration phase or has not produced yet, there would be value creation for all stakeholders involved particularly community.Keywords: CSR, Stakeholder Theory, Competitive, Value Maximizing